Comparación de Microbiota de vulva y tracto vaginal en yeguas destinadas para reproducción - Herreño Cárdenas, Cindy Johanna; Fajardo Garay, Paula Estefany (Universidad Antonio Nariño, 2022)
The microbiota that remains in the vulva is beneficial because its role is to build a protective barrier against potentially pathogenic microorganisms that can cause vaginal an uterine infections and problems. The objective of this study is to determine the similarity of the microbiota of the vulva and vaginal tract of mares intended for reproduction. Microbiological cultures of samples collected from the vaginal and vulva tracts of breeding mares from the municipality of Tenjo (Cundinamarca) were carried out.